Development of Information System using Scrum Model : (Case study: Al-Muayyad Windan Islamic Boarding School) - Fadliansah, Arafik Nur; Prakisya, Nurcahya Pradana Taufik; Aristyagama, Yusfia Hafid; Jimsan (Jurnal Media Informasi Teknologi, 2025)
Islamic boarding schools (pesantren) are Islamic educational institutions in Indonesia that must adapt to technological developments. Developing a digital-based management information system is one of the solutions to support effective data management and administrative processes. However, data collection at Al-Muayyad Windan Islamic Boarding School is still carried out conventionally, which often causes inefficiency in managing student information. Therefore, this research aims to develop a student management information system using an agile software development methodology, namely the Scrum model, which allows iterative development and continuous feedback. The implementation of Scrum was successfully carried out through stages including Product Backlog, Sprint Planning, Sprint Backlog, Sprint, Sprint Review, and Retrospective. The resulting system has passed feasibility testing and usability evaluation. The SUS test involving 10 respondents produced an average usability score of 73, categorized as Acceptable on the Acceptability Range, Grade C on the Grade Scale, and Good on the Adjective Rating. These results indicate that the developed system is functionally feasible, user-friendly, and capable of supporting digital transformation in Islamic boarding school management.